Financial accounting and reporting (fundamentals) - Millan, Zeus Vernon (Baguio City)
This book is about the fundamentals of Financial Accounting and Reporting. It discusses the basic concepts that underlie the recording, classifying and summarizing of accounting information. The first ten chapters of this book relate to the accounting for sole proprietorship business. The last six chapters introduce the basic concepts in the accounting for partnership and corporate businesses.
Keywords: Accounting; Financial statements